2008
DOI: 10.1029/2007jd008657
|View full text |Cite
|
Sign up to set email alerts
|

Size‐resolved chemical composition of aerosol particles during a monsoonal transition period over the Indian Ocean

Abstract: [1] An aerosol time-of-flight mass spectrometer (ATOFMS) was used to measure the sizeresolved mixing state of particles over the northern Indian Ocean in October and November 2004. This period was chosen to observe the impact of the monsoonal transition on the size, chemistry, sources, and radiative properties of atmospheric aerosols in the region. Overall, elemental carbon with sulfate (EC-sulfate), biomass/biofuel burning, fresh sea salt (SS), aged sea salt, fly ash, and EC mixed with sea salt were the domin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
46
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 63 publications
3
46
2
Order By: Relevance
“…It is important to note that KeNa-rich type was observed in 11.9% of the particles. The color stacks of the carbon cluster ions peak demonstrate that approximately 90% of the KeNa-rich particles internally mixed with EC ( Figure S3), which differs from the sea salt particles (Dall'Osto et al, 2004;Dall'Osto and Harrison, 2006;Spencer et al, 2008). Pearson correlation analysis indicated that the unscaled SPAMS counts in 1 h resolution of certain particle types have a correlative relationship, particularly between KeEC and KeNarich (correlation coefficients r ¼ 0.894, p < 0.01) ( Table S1).…”
Section: Chemical Compositionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to note that KeNa-rich type was observed in 11.9% of the particles. The color stacks of the carbon cluster ions peak demonstrate that approximately 90% of the KeNa-rich particles internally mixed with EC ( Figure S3), which differs from the sea salt particles (Dall'Osto et al, 2004;Dall'Osto and Harrison, 2006;Spencer et al, 2008). Pearson correlation analysis indicated that the unscaled SPAMS counts in 1 h resolution of certain particle types have a correlative relationship, particularly between KeEC and KeNarich (correlation coefficients r ¼ 0.894, p < 0.01) ( Table S1).…”
Section: Chemical Compositionmentioning
confidence: 99%
“…Single particle mass spectrometer, such as aerosol time-of-flight mass spectrometer (ATOFMS), has been extensively used to measure the aerodynamic size and chemical composition of individual aerosol particles (Gard et al, 1997(Gard et al, , 1998Guazzotti et al, 2001;Liu et al, 2003;Toner et al, 2006;Shields et al, 2008;Spencer et al, 2008;Pratt and Prather, 2009). It has been proved to be a powerful tool for analyzing the mixing state and formation mechanisms of aerosols in single particle levels (Gaston et al, 2010;Angelino et al, 2001;Moffet et al, 2004;Freney et al, 2006;Denkenberger et al, 2007;Moffet and Prather, 2009;Wang et al, 2009a;Yang et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The presence of secondary species on the particle types provides an indication of chemical processes in the atmosphere (Spencer et al, 2008). Several secondary markers (i.e., m/z 18, −46, −62 and −97) and other markers (m/z −35/−37 for chloride, and m/z 36 for carbon) are selected to show their association with each particle types.…”
Section: Mass Spectral and Mixing State Characteristics Of The Particmentioning
confidence: 99%
“…The recent emergence and development of single particle mass spectrometry technology has been significantly advancing ambient individual particle characterization (Pratt et al, 2009;Su et al, 2004). It has been utilized to characterize size and mixing state of both ambient and laboratory generated aerosols, greatly improving the understanding on the aging processes, source, and optical properties of atmospheric aerosols Spencer et al, 2008;Sullivan et al, 2007). In China, on-line single particle mass spectrometry has most recently been applied in the studies on physicochemical properties of individual particles and their potential influence on air quality (Chen et al, 2014;Yang et al, 2012), and the related researches have investigated the mixing state of carbonaceous particles in the atmosphere of the PRD region Zhang et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Single particle mass spectrometers, such as the aerosol time-of-flight mass spectrometer (ATOFMS), have proven valuable in identifying and characterising a wide variety of particle sources: sea salt, mineral dust, vehicle exhaust, tyre wear, solid fuel combustion (coal, peat and wood), shipping and various industrial emissions Bhave et al, 2001Bhave et al, , 2002Dall'Osto et al, 2014;Giorio et al, 2012;Harrison et al, 2012;Healy et al, 2009Healy et al, , 2010Healy et al, , 2012Liu et al, 2003;Spencer et al, 2008;Tao et al, 2011). Mixing state information -both internal and external -provided by mass spectrometers has been used to determine the type of atmospheric processing particles have undergone (Gard et al, 1998), as well as their acidity and hygroscopicity (Denkenberger et al, 2007;Healy et al, 2014), properties which affect their ability to act as CCN (cloud condensation nuclei; Furutani et al, 2008).…”
Section: Introductionmentioning
confidence: 99%